(636) The Balance of The National Economy (Part I: Theoretical Principles of the Balance of National Economy) ,(Part II: The Balance of Production and Utilization of Social Product) ميزان الاقتصاد الوطني (الجزء الأول: المبادئ النظرية لميزان الاقتصاد الوطني)، (الجزء الثاني: ميزان إنتاج واستخدام المنتج الاجتماعي) - Spevacek, Vojtech (INP, 2024)
paper